Pengaruh Financial Technology Penggunaan E-Wallet dan QRIS Terhadap Perilaku Konsumtif Gen Z di Kota Mataram - Ida Ayu Wayan Sudesni Netiliani; Ni Luh Putu Anom Pancawati; Ida Ayu Nyoman Widia Laksmi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of Fintech E-Wallet and QRIS usage on the consumptive behavior of Generation Z in Mataram City. This research employed a quantitative approach with a sample of 100 respondents selected through purposive sampling. Data were analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, and F-test. The results indicate that: (1) the use of Fintech E-Wallet has a significant effect on the consumptive behavior of Generation Z in Mataram City; (2) the use of QRIS does not have a significant effect on the consumptive behavior of Generation Z in Mataram City; and (3) simultaneously, Fintech E-Wallet and QRIS have a significant effect on the consumptive behavior of Generation Z in Mataram City. The coefficient of determination shows that 18% of the variation in consumptive behavior can be explained by the two variables, while the remaining 82% is influenced by other factors outside the scope of this study.